Frecuencia de leptospirosis y posibles factores de riesgo asociados en hatos caprinos de la parroquia Zapotillo del cantón Zapotillo - Villavicencio Pardo, Carlos Enrique (2023)
Leptospirosis is a disease caused by a spirochete-shaped bacteria called Leptospira spp wich can be transmitted from animals to humans and it is considered a public health problem worldwide, particularly in tropical, subtropical, and temperate areas. There are various species of Leptospira distributed around the world, the most prevalent in Ecuador affecting goats, sheep, and cattle: hardio, pomona, grippotyphosa and ballum. Laboratory diagnosis is complex; however, in recent years, techniques such as the macroscopic agglutination test (MAT) have been described, which is highly specific for timely detection of the disease. In the Zapotillo Parish, the presence of Leptospirosis has been detected in goat herds, which manifests itself with acute clinical signs such as fever, anorexia, and blood in the urine. Therefore, the objective of this work was to determine the frequency of leptospirosis in goat herds in Zapotillo Parish, identifying the serovars existing in the goat population, and determining the possible risk factors associated with the presence of Leptospira spp. The study was carried out with a total of 50 samples collected from ten different herds in the canton. For the analysis of serum sample, MAT was applied with live antigens, and an epidemiological survey was used to the owners of the different herds in order to determine possible risk factors. A prevalence of Leptospirosis of 16% was found, detecting the following serovars: Lictero (3%), L. pomona (2%), L. canicola (1%), and L. hardio (2%) and no animals showed positivity to more than one serovars. As for the risk factors, the presence of rodents was found in 90% of goat herds of the Zapotillo Parish from Zapotillo Canton.